Strategic Brand Engagement: Colgate's Case Study Initiative and Curriculum Innovation - Bagde, Tanishk (ATLAS SkillTech University, 2025)
This black book documents my internship at Colgate-Palmolive, where I worked as a marketing and branding intern. Through this journey, I contributed to two major projects: developing a case study for potential publication in the Harvard Business Review and designing a curriculum for Tier 1 business schools in Mumbai. All these works were relevant to the strategic goals of increasing brand engagement and creating an educational collaboration for Colgate-Palmolive. First off, the case study was one looking to shed light on innovative strategies in Colgate- Palmolive branding and underline their leadership in FMCG. In essence, it requires comprehensive research with data analysis, all combining very strongly to make a case study in interdisciplinary collaboration. Another was to develop a curriculum that would be adopted into the MBA programs of top business schools. The curriculum was designed with an idea of merging theoretical knowledge with practical applications in a bid to prepare students for real challenges in the areas of marketing and branding. The initiative had been a part of Colgate-Palmolive's strategy aimed at engaging with academic institutions for purposes of developing future industry leaders. The following report provides an in-depth review of the methodologies of such projects and challenges and outcomes involved. This reflects how they correspond to the larger strategic objectives set down by Colgate-Palmolive. It also looks at the skills and knowledge gained, including project management, strategic communication, and corporate strategy at the juncture of educational initiatives. This black book concludes with some recommendations toward further branding and educational strategies at Colgate-Palmolive, based on the insights and experiences gained during my internship.
Project Report on Strategic Brand Engagement: Colgate's Case Study Initiative and Curriculum Innovation (2023-2025) Under the Guidance of Prof. Poonam Singh
Keywords: marketing; branding; educational collaboration; strategic communication; project management; corporate strategy; educational strategies